Prime-Boost Vaccine Regimen for SjTPI and SjC23 Schistosome Vaccines, Increases Efficacy in Water Buffalo in a Field Trial in China - Da'Dara, Akram A.; Li, Changlin; Yu, Xinling; Zheng, Mao; Zhou, Jie; Shollenberger, Lisa M.; Li, Yue-sheng; Harn, Donald A. (Frontiers in Immunology, 2019)
Schistosomiasis remains a serious zoonotic diseas in China and the Philippines. Water buffalo and cattle account for the majority of transmission. Vaccination of water buffalo is considered a key strategy to reduce disease prevalence. Previously, we showed that vaccination of water buffalo with SjC23 or SjTPI plasmid DNA vaccines, induced approximately 50% efficacy to challenge infection. Here, we evaluated parameters aimed at reducing the vaccine regimen to two doses while increasing vaccine efficacy. We performed four trials to evaluate 1) lab produced vs GLP grade vaccines, 2) varying the time between prime and boost, 3) the influence of an IL-12 adjuvant, and 4) a two dose heterologous (DNA-protein) prime-boost. We found that the source of the DNA vaccines did not matter, nor did increasing the interval between prime and boost. Elimination of the IL-12 plasmid lowered homologous DNA-DNA vaccine efficacy. A major finding was that the heterologous prime boost improved vaccine efficacy. Further, the heterologous prime-boost regimen incorporating both antigens yielded the highest levels of efficacy we have seen, 55% reduction in adult worms and 53% reduction in liver eggs. Vaccinated buffalo produced vaccine-specific antibody responses. These trials suggest that highly effective vaccination against schistosomes can be achieved using a two dose regimen. Further, as no adjuvant was utilized during the protein boost, we believe incorporating an adjuvant will yield higher levels of efficacy. These results suggest that use of these two schistosome vaccines can be part of an integrated control strategy to reduce transmission of schistosomiasis in Asia.